Ancient Disaster, the Cause of the Burial of the Kumitir Archeological Site - Widodo, Amien; Rochman, Juan Pandu Gya Nur; Fajar, M. Haris Miftakhul; Roslee, Rodeano; Nugroho, Wicaksono Dwi (Faculty of Geography, Universitas Gadjah Mada, 2024)
The Kumitir site, associated with the Majapahit Empire, is a significant archeological discovery. Archeologists from the East Java Cultural Heritage Preservation Center (BPCB), uncovered a structure at this site, buried beneath boulder-sized rocks. According to historical literature, the collapse of Majapahit was caused by volcanic eruptions from the Anjasmoro, Arjuno, or Welirang complexes. Therefore, this study aimed to recreate the gravity-driven mass flow covering the Kumitir Site. Geological surveys, including sediment structure analysis and grain orientation measurements, were conducted to provide new information on paleocurrent and ancient sedimentary processes at the site. Digital Elevation Map (DEM) and the Laharz simulation tool facilitated the creation of reconstructed lahar flow maps using open-source DEM data with an eight-meter resolution. The results of the boulder analysis showed that a paleochannel played a significant role in the burial site, with two sources identified, namely Mount Welirang (Welirang alluvial fan) and the Anjasmoro complex (Old Jatirejo alluvial fan). Meanwhile, the combination of methods applied signified the direction of the Welirang alluvial fan (ESE-NNW) and the Jatirejo Tua alluvial fan (SSW-NNE). Volumes of 9 million m3 and 65 million m3 were the most relevant parameters for estimating the lahar flows of the western and eastern craters, respectively.